Propane Hydrogenolysis over Alumina-Supported Pt-Rh Catalyst - H. EL KHATIB, FAYEZ; S. MAHMOUD, SABRI (Asian Journal of Chemistry, 2010)
Bimetallic catalysts of various Pt/Rh ratios supported on Al2O3 have been prepared and used in propane hydrogenolysis reaction. The reaction order with respect to hydrogen was determined and found to equal -2 indicating inhibiting action of hydrogen. The activation energy of propane hydrogenolysis was calculated for Rh, Pt30-Rh70 and Pt50-Rh50 and found to have the following values: 201, 221 and 201 kJ/mol, respectively. The effect of %Rh mass content on the reaction rate was also studied.